Efecto citotóxico del extracto acuoso de las hojas de Annona Cherimola en una línea celular de cáncer de pulmón en medio cultivo con pH ácido - Medina Lanche, Mayra Alexandra (2015)
The Acetogenins which belong to the genre Annona in several intra-laboratory tests have shown their cytotoxic activity against tumor cells; therefore we have developed the following investigation with an experimental-perspective design guided to evaluate the cytotoxic effect of aqueous extracts from the Annona cherimola leaves in the line cell of lung cancer with a medium crop of Ph. acid, its focused to determine the grade/level of proliferation and the viability of A-549 cells versus the extract of the proliferation cell technique which consists on assessing the cell development meanwhile its viability (living-dead) was determined through blue staining tripán every 6 hours during 4 days. In order to conclude this study we used a positive control (cells a-549 in front of cisplatin) and a negative control (cells A-549 in front of the medium crop Roswell Park Memorial Institute (R.P.M.I.) completed) in order to control the quality of the study. The proliferation cell degree in A-549 versus the extract aqueous from the Annona ch. leaves in different concentrations (concentrated, 1:10-1:50) in 6 hours’ time gives a 0% of confluence meanwhile in 36 hours of different concentration we can clearly obtain a 74,4%, 71,9% y 80,5% ; nevertheless at 72 hours his development is diminished acquiring the following values 68,2 %, 61,1% and a 64,7%; meanwhile in order to assess its cell viability an 82,2% of cytotoxicity was acquired with the medicine, and a 34,4% in extract while normal cells, versus the diluted 1:10 extract from the Annona ch. leaves develop a 10,9% during the first 72 hours of incubation. Finally we can conclude the level of cytotoxicity from the extract from the Annona ch. leaves versus the cells A-549 and Mo nuclear is very low in relation to the cisplatin which causes a high cytotoxicity. Key Words: - Annona Cherimola, Acetogenins, Cytotoxicity, pH acid, Lung cancer, Proliferation Cellular and Viability Cellular.